2021
DOI: 10.1002/cncr.33683
|View full text |Cite
|
Sign up to set email alerts
|

Validating the Patient‐Reported Outcomes Measurement Information System Short Form v1.0–Anxiety 8a in a sample of young adult cancer survivors: Comparison with a structured clinical diagnostic interview

Abstract: Background The objective of this study was to validate the Patient‐Reported Outcomes Measurement Information System Short Form v1.0–Anxiety 8a (PROMIS‐A‐SF) against a structured diagnostic interview in order to determine its accuracy and the most appropriate cutoff score for identifying anxiety disorders in young adult cancer survivors (YACSs). Methods Two hundred forty‐nine YACSs aged 18 to 40 years (50% male) completed the PROMIS‐A‐SF and the Structured Clinical Interview for the Diagnostic and Statistical M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 43 publications
1
8
1
Order By: Relevance
“…Previous research has found increased levels of distress among YA cancer survivors compared to age-, sex-, and education-matched controls [ 45 ]. On the other hand, mean anxiety and depression scores in our study were low compared to existing thresholds that have been previously assessed in YA cancer survivors [ 46 , 47 ].…”
Section: Discussioncontrasting
confidence: 84%
“…Previous research has found increased levels of distress among YA cancer survivors compared to age-, sex-, and education-matched controls [ 45 ]. On the other hand, mean anxiety and depression scores in our study were low compared to existing thresholds that have been previously assessed in YA cancer survivors [ 46 , 47 ].…”
Section: Discussioncontrasting
confidence: 84%
“…Future research should examine the utility of existing measures (e.g., GAD-7 33 ) to determine if any are more effective as a second step in screening than the PRIME-MD anxiety diagnosis threshold. Although a single measure would be preferable, the lack of consensus on a brief validated screening measure for anxiety in YACS 4,5,14 means that a two-step screening process using the PRIME-MD could be useful until an appropriate single measure has been established.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were a convenience cohort of survivors recruited from a single cancer center to participate in E-Quest, a study examining screening methods for depression and anxiety in YACS. As previously described, [12][13][14][15] individuals were eligible if they were 18-40 years old, English-speaking, at least 3 years from their first cancer diagnosis, and at least 2 years since completion of cancer treatment. As has been previously described, 16,17 cancer types, treatments, and treatment settings vary significantly across the age span from childhood through young adulthood.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parental self-reported anxiety was measured using the Patient Reported Outcomes Measurement Information System Short Form v1.0-Anxiety 8A (PROMIS-Anx), an 8-item self-report measure of anxiety symptoms experienced over the previous 7 days. Raw scores are converted into t -scores on the basis of published PROMIS scoring guidelines, 36 where t -scores 0–55 indicated little concern for anxiety, 55–60 indicated mild symptoms of anxiety, 61–70 moderate clinical concern for anxiety, and scores 70 or above suggested clinical concern for anxiety disorder. 37 Previous research has shown that the PROMIS-Anx has strong psychometric properties including internal validity (Cronbach’s α = 0.93–0.95), 38 , 39 reliability (Intraclass Correlation Coefficient [ICC] = 0.79), 39 and relatively invariance across ethnically diverse subgroups.…”
Section: Methodsmentioning
confidence: 99%